LONG TERM HYDROLOGIC BALANCE OF THE CITARUM BASIN AND JAVA ISLANDKESEIMBANGAN HIDROLOGI JANGKA PANJANG DAS CITARUM DAN PULAU JAWA - Hidayat Pawitan (Agromet, 2002)
Abstract is available in the full text (pdf format)